Phenomenon of the complete suppression of cardiac activity in the Black Sea scorpionfish Scorpaena porcus (Scorpaenidae) during an alertness reaction - E. E. Kolesnikova (A. O. Kovalevsky Institute of Biology of the Southern Seas of RAS, 2021)
Teleosts serve as experimental models for the physiological and pathophysiological processes investigation, in particular those related to the heart work. Methods allowing to analyze the frequency parameters of the heart functioning over a long period of time require taking into account the peculiarities of fish behavioral reactions, that can affect the results of the experiment. The aim of this study was to examine the effect of the simplest test loading (sound stimulus) on the frequency parameters of the heart activity recorded by the fiber-optic method. The objects of the study were adults of Scorpaena porcus (12–15 cm long, 80–120 g in weight). In the course of experiments, each scorpionfish was kept in a separate aquarium with seawater (400×400×350 mm), with constant temperature (21 ± 0.5) °C and given oxygen content (5.5–6.7 mg·L−1, normoxia). The heart rate (HR) recording was carried out by an invasive fiber-optic method, the essence of which is to transmit the radiation of the infrared semiconductor laser of the photoplethysmograph through a thin fiber-optic cable to the pericardial membrane of the heart and then to fix the signal reflected from the contracting myocardium in the photodetector. During implantation of the photoplethysmograph light guides, the fish were anesthetized by placing them in an anesthetic solution (urethane, 2.4 g·L−1 of seawater). In the fornix of the opercular cavity above the area of the conditional heart projection, a minimal dissection of the lining epithelium was performed, through which the underlying tissues were sequentially separated by a blunt method until the pericardial membrane was reached without breaking it. Through the lumen formed in the tissues, two optical light guide sensors were introduced to the surface of the pericardial membrane. Further, free-swimming scorpionfish participated in the experiment after a day of rehabilitation after the surgery. Additionally, we assessed the functional state of the animals by visual fixation of respiratory activity by the quantity of movements of the opercular covers per minute. During studying the test loading effect on the correct registration of the scorpionfish HR, the phenomenon of temporary complete suppression of cardiac activity was revealed, which manifested itself upon presentation of sound stimuli (alertness, “freezing” reaction). The duration of cardiac arrest was 31 to 50 seconds; it was accompanied by the cessation of movement of the opercular covers (respiratory arrest, apnea). During the restoration of cardiac activity, two types of physiological reactions were noted. The first type of recovery reaction was characterized by a simultaneous 1.5-fold increase in the HR and a 2-fold enhancement in the photoplethysmograph signal amplitude. The second type of reaction was accompanied by a rise in the HR by 22 % (p < 0.05) against the backdrop of a decrement in the signal amplitude of the photoplethysmograph sensors by 28 % (p < 0.05); within   120 seconds, the scorpionfish HR returned to baseline. It is assumed that the short-term delay in the scorpionfish cardiac activity is based on the phenomenon of cardiorespiratory coupling and synchronization. The behavioral reaction in the form of suppression for the cardiac and simultaneously respiratory activity generation ensures the complete absence of acoustic and electrical signals, which unmask an ambush predator location, and contributes to the scorpionfish survival.